2013
DOI: 10.1080/10426914.2013.763967
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Residual Stresses on the Accuracy of Parts Processed by SPIF

Abstract: The aim of the present work was to investigate the residual stresses distribution within parts processed by single point incremental forming (SPIF) as a function of the working parameters and to determine its influence on the parts accuracy. The study was performed for a double frustum of pyramid made by 304 stainless steel. An experimental analysis was first conducted by using the strain-rosette method. Since the method allowed determining the residual stresses only locally, a numerical model was then elabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Effect of the highest peak of the surface Sp on the variation of (a) axial and (b) tangential residual stresses in the outer surface of a drawpiece formed at step size ap = 0.5 mm. An increase in step size causes an increase in the axial (Figure 16a) and tangential (Figure 16b) residual stresses, as was also found by Radu et al [25] and Jimenez et al [46]. By increasing the tool step-down, the magnitude of the compressive residual stresses on the non-contact surface also increases when forming pyramidal drawpieces [17].…”
Section: Residual Stressessupporting
confidence: 72%
See 2 more Smart Citations
“…Effect of the highest peak of the surface Sp on the variation of (a) axial and (b) tangential residual stresses in the outer surface of a drawpiece formed at step size ap = 0.5 mm. An increase in step size causes an increase in the axial (Figure 16a) and tangential (Figure 16b) residual stresses, as was also found by Radu et al [25] and Jimenez et al [46]. By increasing the tool step-down, the magnitude of the compressive residual stresses on the non-contact surface also increases when forming pyramidal drawpieces [17].…”
Section: Residual Stressessupporting
confidence: 72%
“…The results indicated compressive residual stresses with a magnitude that varies through the sheet thickness. In another paper, Radu et al [25] investigated the effect of residual stresses on the accuracy of parts processed by SPIF using the strain-rosette method. The results of the investigations revealed that a favorable state of residual stresses, and implicitly a good accuracy of parts, can be obtained when small values of tool diameter and vertical step sizes are used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hole drilling method was used to experimentally analyze the magnitude of the residual stresses. In another study, Radu et al [12] developed a cause-effect relationship between the process parameters, residual stresses, and the geometrical accuracy. They concluded that the residual stresses decrease by increasing the tool diameter and spindle speed, whereas the residual stresses increase by increasing the tool step-down and feed rate.…”
Section: Introductionmentioning
confidence: 99%
“…Shrinkage was inevitable when the core pattern was too thick. To find out if the core dimension error is the main reason of the wall-thickness variation, the 3D laser scanner was used to measure the injected core pattern [14][15][16]. Then the error between a theoretical model and points cloud data is compared.…”
Section: Analysis Of Mechanism Of Core Deflectionmentioning
confidence: 99%